Behaviors of Large-Rupture-Strain Fiber-Reinforced Polymer Strengthened Reinforced Concrete Beams Under Static and Impact Loads - Ye, Zenghui; Zhao, Debo; Sui, Lili; Huang, Zhenyu; Zhou, Xiaoqing (Frontiers in Materials, 2020)
Reinforced concrete (RC) structures may be damaged seriously when subjected to impact loading, and it is necessary to strengthen existing structures to improve their impact resistance. Large-rupture-strain FRP (LRS-FRP) is a promising material to strengthen RC structures under impact because of its good deformation capacity. The paper conducted experimental studies on performances of LRS-FRP strengthened RC beams under static and impact loads. The influences of FRP types, impact weight and velocity, and whether applying end anchorages on the strengthening efficiency were investigated. The end anchorage LRS-FRP strengthening system reduced the maximum deflection and damage of strengthened beam significantly. However, the end anchorage was more susceptible to damage and failure under impact. Therefore, the end anchorage and the EA-FRP connection should be designed with caution for impact condition.